Curriculum Management of Biological Sciences During the Outbreak of Covid-19 (A Study at Sekolah Menengah Atas 1 Polanharjo Klaten) - Wisacita, Miranti; Raharjo, Tri Joko; Utanto, Yuli (Educational Management, 2021)
A curriculum is a set of guidelines created by educational institutions to achieve learning objectives. Therefore, there needs to be a management system that is usually called curriculum management. This study aims to analyze the management of the biological sciences curriculum during the outbreak of Covid-19. This research uses a descriptive qualitative approach that focused on curriculum management activities: planning, organizing, implementing, and evaluating. The main data source is the vice principal of curriculum affair and Biology teachers. For the supporting data are the students of XI MIPA. The data collection techniques are gathered through interviews, observations, and documentation. Finally, the results show that the syllabus and lesson plan are carried out to formulate the curriculum in an emergency. They are supervised directly by the vice principal of curriculum affair: task sharing, arranging the biology teacher schedule, and determining the study load in organizing activities. The implementation activities will be seen how the implementation of the Biology curriculum, learning process, and supervision by the vice principal of curriculum affair and their team. There will be a meeting of the new school year period for the evaluation activities, a meeting of the midterm period, and a meeting of the semester. It can be concluded that the process of curriculum management of biological sciences in the outbreak has been running well, although some things need to be improved.